1998
DOI: 10.1046/j.1365-2842.1998.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four different denture cushion adhesives – a subjective study

Abstract: Four cushion adhesives (Fittydent I; Fittydent II, introduced as an advanced formula; Protefix; and Seabond) were compared clinically through patients subjective evaluations. Maxillary dentures of 32 patients were relined and the mandibular dentures were scored by Kapur index before the application of different treatments. The cushion adhesives were used only with the existing mandibular prosthesis. The four treatments were applied to the patients in groups of 8 by allocating each group randomly to one of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 10 publications
2
37
0
2
Order By: Relevance
“…Fittydent paste adhesive was found to be more effective than powder and strips type of adhesive and also, the powder type of denture adhesives were found to be more effective than strips type of adhesive. These findings are in accordance with the studies by Uysal et al11 and Kulak et al12…”
Section: Discussionsupporting
confidence: 94%
“…Fittydent paste adhesive was found to be more effective than powder and strips type of adhesive and also, the powder type of denture adhesives were found to be more effective than strips type of adhesive. These findings are in accordance with the studies by Uysal et al11 and Kulak et al12…”
Section: Discussionsupporting
confidence: 94%
“…In any case, many clinicians are uncertain about the true efficacy of such products, and are not sure about which adhesives offer the best retention performance. Many authors (6-8) consider these products to improve denture stability and retention, though almost all the research published in the literature consists of in vitro studies (9) and/or is based on the administration of patient satisfaction questionnaires (10,11). Of the limited in vivo studies carried out to date, most involve the upper maxilla (12), and only a few involve the mandible (13).…”
Section: Discussionmentioning
confidence: 99%
“…An ideal denture adhesive should retain its adhesive properties for 12 to 16 h before requiring re-application 12) , and the initial viscosity should allow easy manipulation without compromising the adhesive strength. Koronis et al 11) and Uysal et al 15) found that only 68-75.7% of people surveyed reported that the retentive capacity of denture adhesives lasted for more than 2 h. However, several other studies reported that denture adhesives can remain effective for more than 8 h 16,17) , with the retentive capacity peaking at 2 to 4 h after application 16,17) , Influence of composition on the adhesive strength and initial viscosity of denture adhesives Jian- 16,17) . In our preliminary study, a lot of commercial denture adhesives were the tendencies that the adhesive strength decreased after immersed into water for 1-2 h. However, in the clinical situation, it is necessary that the maximum adhesive strength can be lasted for more than 6 h. The small period of effective retention offered by denture adhesives may be the reason why some denture wearers apply them several times a day in order to keep their dentures in place.…”
Section: Introductionmentioning
confidence: 99%